PROMOTING CULTURAL AWARENESS THROUGH LANGUAGE LEARNING - Abdugafforova Nozima Farhod Ogli (Western European Studies, 2024)
This article examines the role of language learning in promoting cultural awareness. By integrating cultural elements into language instruction, educators can help students develop a deeper understanding of diverse cultures and enhance their intercultural communication skills. The article discusses various strategies for incorporating cultural content into language lessons, including the use of authentic materials, cultural activities, and crosscultural exchanges. It highlights the benefits of fostering cultural awareness through language learning and provides practical examples for educators to implement in their classrooms
Keywords: Cultural awareness; language learning; intercultural communication